Efektivitas Pengelolaan Keuangan Desa Oleh Kepala Desa Bahara Kecamatan Panjalu Kabupaten Ciamis Tahun Anggaran 2022 - Arip Saepul Milah; Arie Budiawan; Irfan Nursetiawan (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
Financial management by the Bahara Village Government is one form of implementing the Village Government's authority to manage village assets, but this has not yet shown optimal implementation because there are still problems in managing village finances, namely: The Village Government is less than optimal in discussing and preparing Cost Budget Plans (WED). Making village financial plans still involves wasteful costs. The research objective to be achieved is to determine the effectiveness of village financial management by the Bahara Village Government, Panjalu District, Ciamis Regency, Fiscal Year 2022. The results of the research are that the effectiveness of village financial management by the Bahara Village Government, Panjalu District, Ciamis Regency, Fiscal Year 2022 has not been implemented optimally. Therefore, the Village Government should be more aware of the aspirations conveyed by the community, providing more firmness for supervisors and workers to pay attention to every direction and managerial time.